L'élargissement ne déclenchera pas une 'explosion des coûts' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
S'adressant au parlement néerlandais, le 21 octobre 2002,...